Colorless tsukuru tazaki and his years of pilgrimage - Murakami, Haruki, 1949- (Vintage Books, 2014)
"The new novel--a book that sold more than a million copies the first week it went on sale in Japan--from the internationally acclaimed author, his first since IQ84"--